Fandom Practices, Collective Construction of Meaning, Identity and Forms of Spirituality: the Case of Jedism - Bertetti , Paolo (E|C, 2024)
Semiotics has always paid little attention to the phenomenon of Fandom. Yet, the different fandom activities are examples of highly significant collective construction of meaning, through which fans organize their personal identity, construct axiologies and can even give rise to new forms of spirituality, as in the case of Jediism, analysed here. Jediism is an “invented religion”: a real cult born within some fringes of the Star Wars fandom who aspire to follow the spiritual path of the Jedi Knights. In an apparently paradoxical form of belief, the different Jediist communities consider George Lucas’ creation – which syncretically mixes philosophical and spiritual materials, from Catholicism to Eastern religions – as a catalyst of pre-existing spiritual and philosophical traditions, from which it draws its value and its own significance.